2021
DOI: 10.1002/jgt.22656
|View full text |Cite
|
Sign up to set email alerts
|

On graphs with no induced five‐vertex path or paraglider

Abstract: Given two graphs H 1 and H 2, a graph is ( H 1 , H 2 )‐free if it contains no induced subgraph isomorphic to H 1 or H 2. For a positive integer t, P t is the chordless path on t vertices. A paraglider is the graph that consists of a chorless cycle C 4 plus a vertex adjacent to three vertices of the C 4. In this paper, we study the structure of ( P 5, paraglider)‐free graphs, and show that every such graph G satisfies χ MathClass-open( G MathClass-close) ≤ true⌈ 3 2 ω MathClass-open( G MathClass-clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Brandstädt and Hoàng [11] showed that (P5,trueP2+P3¯) $({P}_{5},\bar{{P}_{2}+{P}_{3}})$‐free atoms with no dominating vertices and no vertex pairs {x,y} $\{x,y\}$ with N(x)N(y) $N(x)\subseteq N(y)$ are either isomorphic to some specific graph G* ${G}^{* }$ or all their induced C5 ${C}_{5}$s are dominating. Recently, Huang and Karthick [49] proved a more refined decomposition. However, it is not clear how to use these results to prove boundedness of clique‐width of (P5,trueP2+P3¯) $({P}_{5},\bar{{P}_{2}+{P}_{3}})$‐free atoms, and additional insights are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brandstädt and Hoàng [11] showed that (P5,trueP2+P3¯) $({P}_{5},\bar{{P}_{2}+{P}_{3}})$‐free atoms with no dominating vertices and no vertex pairs {x,y} $\{x,y\}$ with N(x)N(y) $N(x)\subseteq N(y)$ are either isomorphic to some specific graph G* ${G}^{* }$ or all their induced C5 ${C}_{5}$s are dominating. Recently, Huang and Karthick [49] proved a more refined decomposition. However, it is not clear how to use these results to prove boundedness of clique‐width of (P5,trueP2+P3¯) $({P}_{5},\bar{{P}_{2}+{P}_{3}})$‐free atoms, and additional insights are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Brandstädt and Hoàng [11] showed that P P P ( , + ) are either isomorphic to some specific graph G* or all their induced C 5 s are dominating. Recently, Huang and Karthick [49] proved a more refined decomposition. However, it is not clear how to use these results to prove boundedness of clique-width of P P P ( , + ) 5 2 3 -free atoms, and additional insights are needed.…”
Section: Proof Of Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…2 . Huang and Karthick [18] showed that if G is (P 5 , paraglider)-free, then χ(G) ≤ ⌈ 3ω(G) 2 ⌉. Chudnovsky and Sivaraman [7] showed that χ(G) ≤ 2 ω(G)−1 if G is (P 5 , C 5 )-free, Brause et al [1] proved that χ(G) ≤ d • ω 3 (G) for some constant d if G is (P 5 , K 2,3 )-free, and Schiermeyer [21]…”
Section: Introductionmentioning
confidence: 99%
“…In the same paper, they further showed that if G is (P 5 , K 1 + (K 1 ∪ K 3 ))free, then χ(G) ≤max{2ω(G), 15}, and they construct an infinite family of (P 5 , K 1 +(K 1 ∪K 3 ))-free graphs such that every graph G in the family satisfies χ(G) = 2ω(G). Huang and Karthick [17] showed that if G is (P 5 , paraglider)-free, then χ(G) ≤ ⌈ 3ω(G) 2 ⌉. Char and Karthick [2] proved that a (P 5 , 4-wheel)-free graph G is 3 2 ω(G)-colorable.…”
mentioning
confidence: 99%